Educação a distância: tendências predominantes na sua expansão, Brasil e Espanha - Guioti, Ednilson Aparecido (2007)
The aim of the research was to analyze the current trends in the development of E-Learning at undergraduate level in the Brazilian context and, in a complementary way the situation in the Spanish context more specifically in Barcelona. The study started from a discussion and analysis of the concept of E-Learning based on the definitions of various authors in order to come to a consensual conceptual what proved to be quite difficult. The initial interest in the development of the on line tutor in E-Learning was minimized as it came to understanding the need for a whole view of the reality in terms of the practices developed in E-Learning and of their development process especially in Brazil. The research question was defined in the following terms: What are the present situation and the main E-Learning trends in Brazil and in Spain? How are the teaching institutions working with E-Learning in the university context, including the development of such professionals who act in the respective contexts? It was proceeded the data colleting of the Brazilian as well as the Spanish situation in the search for information allowing to measure the presence of E-Learning in the universities as well as its limits and possibilities. The statistical data was relevant in order to inform that there are many similarities between both researched contexts and in some cases it was noticed that in the Spanish context there are some new trends which soon may be reproduced in Brazil. Therefore it is necessary and urgent a greater attention by those responsible for E-Learning politics in order to avoid reproducing here the same mistakes found in other realities